The interactive effects of student and teacher variables on students' class participation and achievement - Acosta, Crispiniano R. 1933- (1985)
Data gathered from 32 administrators, 181 teachers and 2,172 students in intermediate and secondary classes in Social Studies, English, Mathematics and Science in Puerto Princesa City public and private schools show that class participation is related to (1) the interaction between responsible-obstructive student classroom behavior and facilitative teacher behavior in elementary science classes; (2) alert-apathetic student behavior in the total sample, the secondary sample, and in secondary mathematics and social studies; and (3) facilitative and integrative teacher behavior. Class achievement is positively related to interactions between (1) dominative teachers and self-controlled excitable pupils in elementary social studies; (2) dominative teachers and confident-undecided elementary English pupils; and (3) facilitative teachers and responsible-obstructive students in secondary English classes. Classroom behavior patterns of teachers and students and teachers sex, civil status and educational attainment are positively related to class participation and achievement.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Student-teacher relationships; Interaction analysis in education; Students -- Rating of